ETIOLOGICAL AND OTHER FACTORS OF HYPERTENSION DEVELOPMENT IN RAILWAY EMPLOYEES - Korzenevskaya, E.P.; Severinovskaya, E.V. (World of Medicine and Biology, 2015)
Presence of arterial hypertension is connected with significant increase in risk of development of cardiovascular complications and the mortality which percent, despite achieved success in treatment of arterial hypertension, remains rather high. Development of sharp complications in drivers is especially dangerous during a shift. Search of new medical technologies from improvement of the results of treatment of arterial hypertensia directed on increase in nonspecific mechanisms of adaptation, functional reserves of cardiovascular system and an elaborationof the updating programs from psychophysiological correction at a polyclinic stage of rehabilitation is actual today.